Dynamic capabilities, operational capabilities (educational-marketing) and performance - Roseli Wünsch Takahashi, Adriana; Bulgacov, Sergio; Maier Giacomini, Mônica (Review of Business Management, 2017)
Purpose – To verify the relationship between dynamic capabilities (DCs) and their impact on performance mediated by operational capabilities, considering educational technological capabilities and marketing capabilities in private higher education institutions (HEIs) in Brazil. Design/methodology/approach – A survey was carried out in 1.932 higher education institutions, resulting in 316 valid insertions. Research involved dynamic capabilities, operational capabilities, performance and environmental dynamism constructs. Findings – The research revealed the emergence and explanation of a competitor model containing relationships that had not been considered by previous models, i.e., the direct influence of technological educational capabilities on marketing capabilities. Originality/value – The results revealed greater managerial complexity when referring to the relationship between DCs and performance, and contribute to research concerning HEIs in Brazil and to academic management itself.